Tahap Penggunaan Teknologi Komputer Di Kalangan Guru-guru Sekolah Menengah Agama Negeri Pahang - Mazli Hasril, Hasarudin (2002)

(untitled)
The purpose of this was to determine the level of knowledge, skills and computer usage among teachers. A total of 175 respondent from Islamic Secondary Schools in Pahang were involved in this study. A questionnaire adopted from Nafisah (1997) was used for this study. The analysis of the data was done descriptively using frequency, percentage and mean. Besides that t-test was used to determine if there were significant differences between the level of computer use with gender, subject taught and computer ownership. One way ANOVA was use to determine if there were significant differences between the level of computer usage with age, teaching experience, academic level and experience in using the computer. In addition, Pearson Corellation was also used to identify the relationship between level of computer use and the level of knowledge and skills. The finding showed that the level of computer use was low (mean = 2.30). Level of knowledge and level of skill was medium with mean value 3.04 and 2.56. The study showed that there were significant differences between level of computer use with all independent variables. The findings also showed that there were significant relationships berween level of knowledge and skills with level of computer use. From this study, a few recommendations were given to increase the level of computer use among teachers. Among them were preparing computer courses and training with the latest software, increasing the number of computer facilities, appointing teachers to look upon damaged computers and collecting funds to buy and repair the computers. Lastly, it is hope that other variables related to computer use will be identified to improve the level of computer use and improve education excellence in Malaysia.